Champs Intel: automatic laptop fan / Nur Ezlan Rohaizad Ibrahim [et al.] - Ibrahim, Nur Ezlan Rohaizad; Mohd Safian, Luthfi Hariz Akmar; Yahya, Muhammad Aiman; Wan Rusdi, Mohamad Aifi; Mohd Zawawi, Muhammad 'Aidil (2018)
Champs Intel is a new company that focused on laptop fans that function automatically that totally new in our industry. Our company located in 20A, Jalan Plumbum P7/P (Floor 1), Seksyen 7, Shah Alam. The main focus of our company is to produce new evolution of laptop fan that can function automatically without using much energy of laptop's battery.